Dual single-cell and bulk RNA sequencing reveal transcriptional profiles underlying heterogenous host-parasite interactions in human peripheral blood mononuclear cells - Chandrasegaran, Praveena; Faydaci, Bekir; Shih, Barbara; Hassan, Musa A. (Frontiers in Immunology, 2025)
Toxoplasma gondii, a zoonotic apicomplexan that infects over a billion people worldwide, can cause early death in immunocompromised individuals and defects in foetal brain development. Toxoplasma is also a major cause of abortion in small ruminants. When Toxoplasma encounters host cells, several outcomes are possible. For example, the parasite can enter the host cell or can inject its effector proteins into the cell without entering. These heterogenous outcomes occur simultaneously in the same host and likely determine disease pathogenesis. Yet, current knowledge of host-Toxoplasma interactions is largely based on averaged responses in bulk cell populations. Here, we employed single cell RNA (scRNA) and bulk RNA sequencing to investigate the transcriptional profiles that underpin heterogenous host-Toxoplasma interaction in human peripheral blood mononuclear cells. We observed that Toxoplasma preferentially infects and elicits transcriptional responses in dendritic cells in human blood. Additionally, we observed that monocytes adopt a dendritic cell-like transcriptional profile over the course of infection. Using genes expressed in sorted host cell populations representative of the different heterogenous host-Toxoplasma interaction outcomes as a reference panel, we show that genes expressed in cells infected via phagocytosis are largely expressed in dendritic cells. Thus, by integrating scRNA and bulk RNA sequencing, our study unveils the transcriptional profiles of diverse Toxoplasma-host cell interaction outcomes, providing novel avenues for targeted investigations into host gene functions during Toxoplasma infections.